Predictors of survival among older adults with HIV in Uganda’s AIDS support organization centers of excellence (1987–2023): a retrospective longitudinal study - Christine Atuhairwe; Leonard Atuhaire; Stephen Ojiambo Wandera; Dinah Amongin; Titus Ochieng; Cyprian Misinde (AIDS Research and Therapy)
Abstract Background The growing number of older adults living with HIV, facilitated by wider access to antiretroviral therapy (ART), presents unique challenges. This study aims to identify predictors of survival among older persons living with HIV receiving ART in Uganda’s AIDS Support Organization Centers of Excellence (1987–2023). Understanding these predictors can inform effective clinical interventions to improve outcomes for this population. Methods This study conducted a retrospective analysis of medical records from 11 TASO centers of excellence in Uganda (1987–2023). Using Cox proportional hazards regression, we identified factors associated with survival among older adults living with HIV. TASO centers of excellence in Entebbe, Gulu, Jinja, Masaka, Masindi, Mbale, Mbarara, Mulago, Rukungiri, Soroti, and Tororo. Cox proportional hazards regression analysis identified factors influencing survival among older persons living with HIV (OPLHIV). Results Of the 30,758 OPLHIV medical records analyzed (1987–2023), 72.5% were active on ART, 5.9% had died, 15.2% were lost to follow-up, and 5.6% transferred to other facilities. Survival was significantly associated with: gender (female, HR = 1.19, p < 0.001), marital status (married, HR = 0.99, p < 0.001; separated/divorced, HR = 0.85, p < 0.001), WHO clinical stage (II, HR = 1.66, p < 0.001), viral load (> 200 copies/ml, HR = 1.49, p < 0.001), and ART adherence (fair, HR = 0.94, p = 0.157). Conclusion Key predictors of survival among Older Adults Living with HIV (OPLHIV) include: female gender, age 50–59, weight 51–70 kg, married status, viral load > 200 copies/ml, WHO HIV clinical stage II, paid employment, and ART adherence. To improve survival outcomes, consistent clinical screenings of WHO clinical stages, viral load, and ART adherence are essential. These measures can guide healthcare providers in making informed treatment decisions to enhance survival and quality of life for OPLHIV in Uganda. Recommendations Strengthen routine monitoring of viral load, ART adherence, and WHO clinical staging. Provide targeted support to married and separated/divorced adults to improve their survival chances. Address gender disparities in care to enhance outcomes for females. Focus on maintaining ART adherence and viral suppression to reduce mortality risks.